The Food and Energy Costs from the Perspective of Sociology of Social Problems (British Journal of Multidisciplinary and Advanced Studies, 2023)
Since human beings are social creatures, it is inevitable for them to live in society. However, many positive or negative changes and developments in society affect people directly or indirectly. At the beginning of the issues that affect the individuals in a society most deeply are the social problems that have emerged in that society. Just as it is not possible to completely eliminate the social problem that has arisen in a society, there seems to be no society that does not experience social problems. In this context, social problems in each society may differ. In addition, while social problems have a continuity feature because they affect many institutions and areas in the society, it has the feature of multi-causality principle because it is based on many different reasons. Likewise, social problems are not social events that occur suddenly or whose effect ends in an instant. In order for such problems to arise, certain conditions and social formations must be present. Because a social issue that arises in one area can be the source or cause of other issues. Recently, especially the problems that have arisen due to economic variables have become a complete social problem. Because the economy, which is an important social institution, is an important concept that affects almost every area of society. In this study, in recent years, a sociological analysis of food and energy costs, which have emerged in many countries in the world due to many different reasons such as Covid-19 pandemic, global warming and climate change, population growth, drought, Russia-Ukraine War, and experienced as a complete social problem, has been started for Turkey. has been studied.